2001
DOI: 10.1007/s004290100163
|View full text |Cite
|
Sign up to set email alerts
|

Topography and distribution of sympathetic nerve fibers in the rat temporomandibular joint: immunocytochemistry and ultrastructure

Abstract: The distribution and fine structure of nerve fibers containing neuropeptide Y (NPY), tyrosine hydroxylase (TH), and vasoactive intestinal polypeptide (VIP) in the temporomandibular joint were investigated by both the avidin-biotin complex method and an indirect immunofluorescence technique. The innervation pattern of NPY- and TH-positive fibers differed from that of VIP-positive fibers. Specifically, the former was distributed in both the superficial and deep sublining layers, while the latter was mostly locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 21 publications
4
15
1
1
Order By: Relevance
“…Some nerves only exhibit PGP 9.5 labeling (red arrows). Bars 50 μm not with TRPV1 seemed to be sympathetic in origin, as demonstrated previously (Kido et al 2001).…”
Section: Mrna Expression Of Trpv1 Receptorsupporting
confidence: 58%
“…Some nerves only exhibit PGP 9.5 labeling (red arrows). Bars 50 μm not with TRPV1 seemed to be sympathetic in origin, as demonstrated previously (Kido et al 2001).…”
Section: Mrna Expression Of Trpv1 Receptorsupporting
confidence: 58%
“…1721 Axons innervating the TMJ contain several neuropeptides, among which are the NPY and the CGRP. 2226 NPY is a 36 amino acid sequence related to the pancreatic polypeptide family. It is synthesized in the rat peripheral nervous system, mainly by autonomic sympathetic and parasympathetic neurons.…”
Section: Introductionmentioning
confidence: 99%
“…3). Kido et al (2001) had also observed a dense NPY innervation in the rat TMJ originating from superior cervical ganglion. Since a similar approach has not been made in any other joint, comparisons were made with previous studies involving the innervation of other orofacial territories.…”
Section: Npy Immunoreactive Neuronal Profiles That Send Nerve Fibers mentioning
confidence: 99%
“…However, very little is known about the possible functions of parasympathetic innervation in the TMJ. In a previous study, it was observed that the removal of the rat superior cervical ganglion resulted in the complete absence of NPY fibers in the TMJ 10 .…”
Section: Npy Immunoreactive Neuronal Profiles That Send Nerve Fibers mentioning
confidence: 99%
See 1 more Smart Citation